Disruption of the Nα-Acetyltransferase NatB Causes Sensitivity to Reductive Stress in Arabidopsis thaliana - Huber, Monika; Armbruster, Laura; Etherington, Ross D.; De La Torre, Carolina; Hawkesford, Malcolm J.; Sticht, Carsten; Gibbs, Daniel J.; Hell, Rüdiger; Wirtz, Markus (Frontiers in Plant Science, 2022)
In Arabidopsis thaliana the evolutionary conserved N-terminal acetyltransferase (Nat) complexes NatA and NatB co-translationally acetylate 60% of the proteome. Both have recently been implicated in the regulation of plant stress responses. While NatA mediates drought tolerance, NatB is required for pathogen resistance and the adaptation to high salinity and high osmolarity. Salt and osmotic stress impair protein folding and result in the accumulation of misfolded proteins in the endoplasmic reticulum (ER). The ER-membrane resident E3 ubiquitin ligase DOA10 targets misfolded proteins for degradation during ER stress and is conserved among eukaryotes. In yeast, DOA10 recognizes conditional degradation signals (Ac/N-degrons) created by NatA and NatB. Assuming that this mechanism is preserved in plants, the lack of Ac/N-degrons required for efficient removal of misfolded proteins might explain the sensitivity of NatB mutants to protein harming conditions. In this study, we investigate the response of NatB mutants to dithiothreitol (DTT) and tunicamycin (TM) induced ER stress. We report that NatB mutants are hypersensitive to DTT but not TM, suggesting that the DTT hypersensitivity is caused by an over-reduction of the cytosol rather than an accumulation of unfolded proteins in the ER. In line with this hypothesis, the cytosol of NatB depleted plants is constitutively over-reduced and a global transcriptome analysis reveals that their reductive stress response is permanently activated. Moreover, we demonstrate that doa10 mutants are susceptible to neither DTT nor TM, ruling out a substantial role of DOA10 in ER-associated protein degradation (ERAD) in plants. Contrary to previous findings in yeast, our data indicates that N-terminal acetylation (NTA) does not inhibit ER targeting of a substantial amount of proteins in plants. In summary, we provide further evidence that NatB-mediated imprinting of the proteome is vital for the response to protein-harming stress and rule out DOA10 as the sole recognin for substrates in the plant ERAD pathway, leaving the role of DOA10 in plants ambiguous.